Progress in the legislations regarding school nutrition lunch and nutrition status in China and some other countries - WANG Wenhui; LIU Yongping; WANG Zhengyuan (Shanghai yufang yixue, 2023)
This paper summarized the school nutrition lunch legislations and nutrition status in China and abroad. School lunch system is relatively well-established and mature in Japan， the United States and Sweden and the lunch system has been gradually as an important part of basic education， which is worth learning by other countries and regions. China started its pilot school nutrition lunch program in 1987， and has improved the nutritional status of students， especially the students in rural areas， significantly. However， there still exists certain gaps compared with developed countries. We should actively learn from those countries， so as to provide reference for the formulation and improvement of China’s nutritional lunch policies.